Genetic Variability in F2 Melon (Cucumis melo L.) Population from Double Cross of Sex-Distinct Parent Lines - Agus Budi Setiawan; Irna Auliauzzakia; Aziz Purwantoro (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Melon (Cucumis melo L.) is an economically significant crop in Indonesia. Due to the increasing demand for premium melon fruit with high sugar content, firm flesh, extended shelf life, bright peel and flesh color, and round fruit shapes, researchers developed melon lines that align with consumer preferences. This study aimed to determine the segregation pattern and genetic basis of sex expression in F1 and F2 populations, estimate genetic parameters for pericarp thickness and total soluble solids, and identify superior F2 genotypes using a predicted selection response based on a weighted selection index. A total of 137 F1 individuals derived from crossing ‘Inthanon RZ’ with ‘Glamour Sakata’ and 237 F2 individuals derived from the self-pollinated IG10 line were grown in a greenhouse using a hydroponic drip fertigation system. The F1 population exhibited genetic variation in sex expression based on the allele-specific marker of CmACS7, with a 1:1 phenotypic ratio, consisting of 68 monoecious and 69 andromonoecious individuals. All individuals in the F2 population showed homozygote andromonoecious expression, indicating that the IG10 progenitor line was homozygous (aaGG). Pericarp thickness and total soluble solids exhibited high phenotypic and genotypic coefficients of variation and moderate-to-high broad-sense heritability. Among the genotypes, four displayed high-weighted selection indices based on the two target traits, with IG10-124 achieving the highest selection index. The selection response based on the weighted selection index suggests that pericarp thickness and total soluble solids will show genetic improvement in the next generation.